Pemodelan Penyebab Balita Stunting Wilayah Pedesaan Kabupaten Bogor - Wiyono, Sugeng; Pritasari, Pritasari; Harjatmo, Titus Priyo; Rachmat, Mochamad; Efiyana, Rina; Astuti, Trina; Ramawati, Siti Mutia; Darmawan, Syarif; Nursanti, Lely; Aruan, Aruni; Marbun, Rosmida M.; Muntikah, Muntikah; Dumaira, Corazon Hanna; James, James (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2024)
Stunting is a syndrome of several pathological changes characterised by linear growth, and underdevelopment at the beginning of life associated with increased morbidity and mortality, physical decline, neurological development, economic capacity, and an increased risk of metabolic diseases into adulthood. Six million children in Indonesia risk losing their intelligence quotient (IQ) of 10 to 15 points. The prevalence of stunting in children aged five years in West Java Province is 20.2% and in Bogor Regency is 18.7%. This research is an analytical research with a sectional cross-section design. The population is all children under five in Leuwiliang District, Bogor, and a sample of 414 children under five. will be held in May 2022. The data were analysed univariately, bivariate, and multivariate. To develop an equation model using multiple logistic regression tests The results of the multivariate analysis review showed that mothers with a height of <150.0 cm were 2.403 times more likely to have short toddlers after controlling for the variables of birth weight and protein intake. Simultaneously, stunting in children under five is caused by mothers with a height of less than 150.0 cm, a birth weight of less than 2500.0 g, and inadequate protein intake. It is sought that from the moment the baby is given good protein for the physical growth and development of the child's brain, maintaining pregnancy so that the baby is born normally (≥2500.0g) and since the child or adolescent consumes a balanced nutritious food so that the height of the woman is 150.0 cm